The Endophyte Trichoderma asperellum M2RT4 Induces the Systemic Release of Methyl Salicylate and (Z)-jasmone in Tomato Plant Affecting Host Location and Herbivory of Tuta absoluta - Agbessenou, Ayaovi; Akutse, Komivi S.; Yusuf, Abdullahi A.; Khamis, Fathiya M. (Frontiers in Plant Science, 2022)
The use of endophytic fungi has dramatically increased plant performance through the enhancement of plant protection against abiotic and biotic stressors. We previously demonstrated that the endophytic fungus Trichoderma asperellum M2RT4 improves tomato defenses against the tomato leafminer Tuta absoluta through the reduction of oviposition, leafmining, pupation and adult emergence. However, the underlying mechanism by which the presence of this endophytic fungus within tomato host plant affects T. absoluta host selection and life-history traits is unknown. We tested the behavioral responses of T. absoluta in Y-tube olfactometer bioassays and found that females preferred healthy tomato plants against those colonized by endophytes. Additionally, T. absoluta females were not attracted to healthy-infested nor to endophytically-colonized infested tomato plants. Chemical analysis revealed the emission of methyl salicylate in endophytically-colonized tomato plant and an increase in the amounts of monoterpenes emitted from T. absoluta-infested plants. Additionally, we found that upon herbivory, T. asperellum M2RT4 modulates tomato plant chemistry through the production of (Z)-jasmone thus activating both salicylic and jasmonic acid defense pathways. Further, T. absoluta females were attracted to monoterpernes including α-pinene, 2-carene and β-phellandrene but repelled by methyl salicylate. Methyl salicylate could therefore be considered as a good semiochemical-based candidate for sustainable T. absoluta management using a “push-pull” approach. However, in dose-response bioassays, females of T. absoluta did not show any preference to the four component-blend (α-pinene, 2-carene, β-phellandrene, and methyl salicylate). (Z)-jasmone-treated tomato leaflets significantly reduced the leafmining activity of the pest at the concentration of 10 ng/µL and causing the highest larval mortality rate (83%) with the shortest LT50 (1.73 days) seven days post-treatment. Trichoderma asperellum M2RT4 effect on herbivore performance was then (Z)-jasmone-mediated. These findings expand our understanding of how the endophytic fungus T. asperellum M2RT4 could mediate chemical interactions between T. absoluta and its host plant which are potentially important for development of environmentally friendly T. absoluta management programs.